AB1385 #rheumjc: 3 year analysis of a twitter based rheumatology journal club. (12th June 2018) - Collins, C.; Campos, J.; Isabelle, A.; Bhana, S.; Jayatilleke, A.; Sufka, P.
Abstract : Background: Twitter is an increasingly popular platform for discussion and engagement amongst healthcare professionals. #RheumJC is a Twitter-based international rheumatology journal club which has occurred approximately once a month for the past 3 years. Here we describe participant analysis and survey results from the past 36 months of this initiative. Methods: A #RheumJC development team, consisting of academic and private practice rheumatologists as well as rheumatology Fellows in Training (FIT), was created to help define the structure and moderate the online discussions. Based on results from an initial needs assessment survey, a structured journal club format was developed. A total of 23 different online journal clubs were conducted between January 2015 and December 2017, each consisting of both "live" one hour chats, as well as a full 24 hours to allow for asynchronous participation for each session. An analysis of the different sessions was performed to assess participant demographics and participation rates. Additionally, follow up surveys were conducted after the 4th, 10th and 23rd journal club sessions to assess metrics of satisfaction and identify additional strengths or barriers to participation. Results: Over the 36 month observation period, a total of 646 individuals from 36 different countries tweeted with the hashtag #RheumJC. Over 90% of these tweets occurred during the live chat sessions. While the majority of participants were rheumatologists, over 10 different medical fields were represented. The Twitter account @RheumJC currently has almost 2700 followers from 36 different countries, with the USA and UK representing the largest numbers of followers (36.4% and 15.7% respectively), and 31.9% of all accounts originating from the European continent. The affiliated mailing list for #RheumJC has over 235 subscribers. The most recent survey (done after the 23rd journal club session) recorded responses from 37 individuals from 13 different countries who indicated they had participated or followed along in at least one of the journal clubs. 74% of the respondents indicated they had participated in at least 2 or more different sessions. The majority (86%) indicated they were either satisfied or very satisfied with the #RheumJC initiative. 31% of respondents admitted that they had only observed some of the sessions and not joined in the actual discussion suggesting that the total number of #RheumJC participants could be greater than the participation data presented here. Of interest, 9% of respondents indicated they had joined Twitter solely because of #RheumJC, and another 29% stated that #RheumJC had increased their use of Twitter as a tool for medical education. The results from this survey closely mimic the responses from prior surveys suggesting an enduring satisfaction with the initiative. Conclusions: #RheumJC is a novel and popular approach to the traditional medical journal club, bringing together people from around the globe and across specialties to discuss current rheumatology literature utilising Twitter as a medium for medical education. Given its continued success for over 3 years now, the #RheumJC initiative has proven itself a valuable addition to the rheumatology medical education community. Disclosure of Interest: None declared